Using of inter dental cleaning`aids among Iraqi dental students - Jawad, Kadhim (Mustansiria Dental Journal, 2005)
ln this study an attempt was made to_ estimate the knowledge and behavior in regard to the use of inter dental cleaning aids among lraqi dental students at different levels of dental study .Two hundred seventy four Iraqi dental student in College of Dentistry, University of Al-Mustansiria were questioned by a suitable questionnaire designed for this purpose about their knowledge and behavior in relation to the use of interdental cleaning measures .Results of this study showed that their information about this subject may need to be reviewed